Outcomes of mechanical thrombectomy at a single-centre tertiary level public health care hospital in South Africa - Kiriinya, Martin (Division of General Surgery, 2025)
Introduction: Mechanical thrombectomy (MT) is standard of care for acute ischemic stroke from large vessel occlusion following randomized controlled trials performed largely in high-income countries. Limited data exists on its effectiveness in the real-world setting, particularly in low- and middle-income countries. We aimed to evaluate the safety and efficacy of MT in a public hospital in Cape Town, South Africa. Methods: We evaluated acute ischaemic stroke patients presenting consecutively to Groote Schuur Hospital between 01 January 2018 to 01 January 2022 with proximal intracranial occlusion in the anterior circulation treated with MT within 6 hours from onset using CT and CTA imaging-based protocols. Demographic, clinical, radiological and procedural data were obtained from the stroke unit database. Recanalization was evaluated post-procedure by modified Treatment in Cerebral Infarction score (mTICI). We assessed functional independence (modified Rankin scores (mRS) 0-2) and mortality at 90 days. Results: Thrombectomies were performed in 84 patients during the study period. The median age was 56 years and 51% of participants were female. Median National Institute of Health Stroke Score was 18 and median baseline Alberta Stroke Programme Early CT score was 8. Bridging thrombolysis was given to 65% of participants. Median time from symptom onset to reperfusion was 339 minutes. Successful recanalization (mTICI 2b/3) was obtained in 62%. At 90 days, 34 % of participants reached functional independence and mortality was 34% . Conclusions: We achieved similar rates of recanalization and functional independence to that seen in trials in high-income countries using basic imaging despite a higher mortality and longer median time to reperfusion. These data support the effectiveness of MT in a public hospital in south Africa despite the challenges of providing emergent stroke care in a resource-constrained setting.